Quantitative detection method for lithium precipitation amount of lithium ion battery

The melting enthalpy of the anode sheet was measured by differential scanning calorimetry and the amount of lithium was calculated, which solved the subjective problem of the determination of lithium anode of lithium in lithium ion batteries in the prior art, realized the accurate detection of lithium anode, and improved the Battery safety and capacity stability.

CN119224037APending Publication Date: 2024-12-31NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310785849.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The determination of lithium anode lithium in existing lithium-ion batteries mainly depends on naked eye judgments, is subjective, and it is difficult to accurately distinguish when the color of the dot lithium-ion and by-products are similar, resulting in safety hazards and attenuation of the battery cell capacity.

Method used

Differential scanning calorimetry (DSC) is used to determine the unit mass melting enthalpy of the anode sheet. The lithium-decomposition amount is calculated by integrating characteristic peaks in the range of 175 to 185°C, and a quantitative detection method is provided to determine whether the anode surface is Lithium evolution occurs and the specific lithium evolution amount is calculated.

Benefits of technology

Accurate detection of lithium anode lithium in lithium-ion batteries is achieved, reducing the impact of subjective judgment, and improving safety and battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119224037A_ABST
    Figure CN119224037A_ABST
Patent Text Reader

Abstract

The invention discloses a quantitative detection method for the lithium precipitation amount of a lithium ion battery, and the quantitative detection method comprises the following steps: S100, circularly treating the lithium ion battery to be detected to a preset SOC, and disassembling the lithium ion battery to obtain an anode plate, S200, carrying out residual electrolyte removal treatment on the anode plate in the step S100 to obtain a pole plate to be detected, and S200, carrying out quantitative detection on the lithium precipitation amount of the lithium ion battery to obtain the lithium precipitation amount of the lithium ion battery. S300, cutting the to-be-tested pole piece in the step S200 to obtain a test sample piece, and obtaining the mass of the test sample piece, and S400, measuring the test sample piece in the step S300 through a differential scanning calorimeter to obtain a DSC curve, integrating the characteristic peaks of the DSC curve within the range of 175-185 DEG C to obtain the melting enthalpy of the test sample piece per unit mass, and calculating the melting enthalpy of the to-be-tested pole piece according to the melting enthalpy of the to-be-tested pole piece. And S500, calculating the lithium precipitation amount of the lithium ion battery according to the melting enthalpy per unit mass of the test sample. Whether lithium precipitation occurs on the surface of the anode or not can be judged, and the lithium precipitation amount can be obtained through calculation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for quantitatively detecting the amount of lithium deposition in lithium-ion batteries. Background Art

[0002] As the energy density of lithium-ion batteries increases, the safety performance of lithium-ion batteries has received more and more attention. Among them, the safety problem of lithium plating at the anode of lithium-ion batteries is one of the common safety issues in the use of lithium-ion batteries. Especially when lithium-ion batteries have high-power fast charging functions, lithium plating at the anode of lithium-ion batteries is not only a safety issue. As the degree of lithium plating deepens, the overall battery capacity decays, the volume expands, and the gas production will also be affected. At present, the determination of lithium plating in lithium-ion batteries is mainly based on the naked eye to determine whether the battery cell has lithium plating after the battery cell is disassembled. The severity of lithium plating depends on the subjective judgment of the individual. The vision and color sensitivity of different individuals have a very large subjective influence on the judgment of lithium plating. Moreover, if the surface of the anode electrode is dotted with lithium plating, the color of this lithium plating is very close to the color of the byproduct, and it is impossible to determine whether it is lithium plating behavior or byproduct deposition behavior. Summary of the invention

[0003] The present application provides a method for quantitatively detecting the amount of lithium deposition in a lithium-ion battery, which can accurately determine whether lithium deposition occurs on the surface of an anode and obtain the specific amount of lithium deposition by calculation.

[0004] In a first aspect, the present application provides a method for quantitatively detecting the amount of lithium deposition in a lithium-ion battery, the method comprising the following steps: S100: cyclically treating the lithium-ion battery to be tested to a preset SOC, disassembling to obtain an anode electrode piece, S200: removing residual electrolyte from the anode electrode piece in step S100 to obtain an electrode piece to be tested, S300: cutting the electrode piece to be tested in step S200 to obtain a test sample, and obtaining the quality of the test sample, S400: subjecting the test sample in step S300 to differential scanning calorimetry to obtain a DSC curve (see Figure 1 As shown), by integrating the characteristic peaks of the DSC curve in the range of 175 to 185° C., the melting enthalpy per unit mass of the test sample is obtained. S500: the lithium deposition amount of the lithium-ion battery is calculated according to the melting enthalpy per unit mass of the test sample.

[0005] In some embodiments, in step S100, cycling the lithium ion battery to a preset SOC includes: charging the lithium ion battery to 100% SOC at 0-5°C at 1-5C, discharging it to 0% SOC at 1-1.5C, cycling for 5-50 cycles, and finally discharging it to 0% SOC at 1-1.5C.

[0006] In some embodiments, in step S100, cycling the lithium ion battery to a preset SOC includes: charging the lithium ion battery to 100% SOC at 0°C 1-5C, discharging it to 0% SOC at 1C, cycling for 10-30 cycles, and finally discharging it to 0% SOC at 1C.

[0007] In some embodiments, in step S200, removing residual electrolyte from the anode electrode piece in step S100 includes: immersing the anode electrode piece in an organic solvent for 0.5 to 1 hour at an ambient temperature of 18 to 35°C, and then standing in a vacuum environment for 0.5 to 1 hour. Too low a temperature (below 18°C) will affect the immersion effect, while too high a temperature (above 35°C) will cause lithium and electrolyte to react. Preferably, at an ambient temperature of 25°C, immerse the anode electrode piece in an organic solvent for 0.5 hour, and then stand in a vacuum environment for 0.5 hour.

[0008] In some embodiments, the organic solvent is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). Preferably, the organic solvent is pure DMC, that is, DMC with a purity of 99.99%.

[0009] In some embodiments, in step S300, cutting the electrode piece to be tested to obtain a test sample includes: cutting the electrode piece to be tested according to the size of the test crucible so that the test sample is in full contact with the bottom of the crucible after cutting, sealing, and obtaining a sample crucible, and placing the sample crucible in a differential scanning calorimeter for testing to obtain a DSC curve of the test sample. It should be noted that the number of times the electrode piece to be tested can be cut can be once or multiple times, and the cutting area at one time cannot exceed the bottom area of ​​the crucible, otherwise it cannot be guaranteed that the test sample after cutting is in full contact with the bottom of the crucible. When cutting multiple times, it is necessary to place the multiple test samples obtained by cutting in turn into a differential scanning calorimeter for testing to obtain multiple DSC curves.

[0010] In some embodiments, cutting the electrode piece to be tested according to the size of the testing crucible includes: cutting the electrode piece to be tested into discs having the same size as the inner diameter of the bottom of the crucible, and laying the discs flat on the bottom of the crucible.

[0011] In some embodiments, in step S300, obtaining the mass of the test sample includes: placing the sample crucible in a weighing balance to obtain the mass of the test sample.

[0012] In some embodiments, in step S400, the parameters of the differential scanning calorimeter during the measurement process include: test temperature: 35-200°C, temperature rise rate: 5-15°C / min, carrier gas atmosphere: inert atmosphere, carrier gas flow rate: 20-120ml / min. If the temperature rise rate is too slow (for example, less than 5°C / min), the DSC sensitivity will decrease, and there may be a problem of not being able to detect the signal; if the temperature rise rate is too fast (for example, higher than 15°C / min), the characteristic peak will shift at high temperature, and the test accuracy will also be affected. Preferably, the test temperature is 35-200°C, the temperature rise rate is 5°C / min, the carrier gas atmosphere is 99.99% helium, and the carrier gas flow rate is 60ml / min.

[0013] In some embodiments, the mass of the sample to be tested is recorded as m (mg), the melting enthalpy per unit mass of the sample to be tested is recorded as ΔH1 (J / g), the theoretical melting enthalpy of lithium is recorded as ΔH0 (J / g), and the area of ​​the sample to be tested is recorded as S (cm 2 ), the lithium deposition amount of the lithium ion battery is recorded as Δm (ug / cm 2 ), Δm is calculated by formula I;

[0014]

[0015] Among them, δ is the correction factor of 0.8, and ΔH0 is 350J / g. Lithium deposition occurs in the battery cell, and a layer of lithium is deposited on the surface of the anode. The theoretical melting point of lithium is 180.5℃, and its theoretical melting enthalpy ΔH0 is 350J / g. The DSC differential scanning calorimeter has high-precision calorimetric characteristics. In addition, the graphite lithium-intercalated compound LixC6 (0≤x≤1) does not have the melting characteristics of metallic lithium. The amount of lithium deposition on the anode surface can be determined by DSC. By integrating the characteristic peak area of ​​lithium deposition in the DSC curve in the range of 180℃, the unit mass melting enthalpy ΔH1 (g / J) of the electrode sample is obtained, and then the amount of lithium deposition can be calculated by the above formula.

[0016] In some embodiments, the detection range of the lithium ion battery lithium precipitation amount is: based on the total weight of the active material layer in the sample to be tested, the mass percentage of the lithium precipitation amount is 0.003-30wt%. Exemplarily, the mass percentage of the lithium precipitation amount is 0.003wt%, 0.005wt%, 0.008wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or the range composed of any two of the above values. It can be seen that the calculation lower limit of the lithium precipitation amount is low and the applicable width is wide.

[0017] In some embodiments, when the number of the test pieces is 1, the melting enthalpy per unit mass of the test piece is obtained by integrating the characteristic peaks existing in the DSC curve within the range of 175-185°C obtained by measuring the test piece by differential scanning calorimetry. When the number of the test pieces is greater than or equal to 2, the melting enthalpy per unit mass of the test piece is obtained by measuring each of the test pieces by differential scanning calorimetry to obtain multiple DSC curves, integrating the characteristic peaks existing in each of the DSC curves within the range of 175-185°C, and then adding the integrated areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 It is a DSC curve diagram obtained by differential scanning calorimetry;

[0020] Figure 2 This is a DSC curve diagram obtained by differential scanning calorimetry of Example 4 of the present application;

[0021] Figure 3 This is a DSC curve diagram obtained by differential scanning calorimetry of Example 5 of the present application;

[0022] Figure 4 It is a linear fitting curve diagram of the theoretical lithium precipitation amount and the measured lithium precipitation amount in Example 4 of the present application;

[0023] Figure 5 This is a linear fitting curve diagram of the theoretical lithium deposition amount and the measured lithium deposition amount in Example 5 of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0025] Preparation of lithium-ion batteries

[0026] Preparation of cathode electrode

[0027] Lithium cobalt oxide, acetylene black and polyvinylidene fluoride were mixed in a N-methylpyrrolidone solvent system at a mass ratio of 97:1.5:1.5, coated on the surface of Al foil and dried to obtain an active material layer, which was then cold pressed to obtain a positive electrode sheet. The mass of the active material layer is 15.92 mg / cm 2 .

[0028] Preparation of anode electrode

[0029] Artificial graphite, acetylene black, styrene-butadiene rubber and sodium methyl cellulose are uniformly mixed in a deionized water solvent according to a mass ratio of 95:2:2:1, coated on one side of a Cu foil, dried, cold pressed and cut to obtain an anode electrode sheet.

[0030] Preparation of isolation membrane

[0031] A 9 μm thick polyethylene (PE) porous membrane was selected as the isolation membrane.

[0032] Preparation of electrolyte

[0033] Ethyl methyl carbonate, ethylene carbonate, lithium hexafluorophosphate, fluoroethylene carbonate, 1,3-propane sultone, and vinyl ethylene carbonate were uniformly mixed in a mass ratio of 40:35:15:3:3:4 to obtain an electrolyte.

[0034] The cathode electrode sheet, the isolation film and the anode electrode sheet are stacked in sequence, the isolation film is used to isolate the cathode electrode sheet and the anode electrode sheet, and a bare battery cell is formed by winding. The bare battery cell is placed in an aluminum-plastic film shell to be sealed, and an electrolyte is injected and sealed.

[0035] The lithium ion batteries in the following Examples 1 to 5 were all prepared by referring to the above preparation method.

[0036] Example 1

[0037] Charge the lithium-ion battery at 0℃3.5C to 100% SOC, then discharge it at 1C to 0% SOC, cycle for 10 weeks, and finally discharge it at 1C to 0% SOC, move it into a glove box for disassembly, and take out the anode electrode for lithium deposition. Because residual electrolyte and deposited lithium will react chemically in the range of 35℃ to 200℃, the residual electrolyte needs to be removed. Specifically, first, immerse the anode electrode in a pure DMC solution for 0.5h, and let it stand at room temperature and vacuum for 0.5h to remove residual electrolyte and DMC. During the above process, the anode electrode cannot be exposed to air and water. The anode electrode is then moved into the glove box for sample preparation. In the glove box, select the anode electrode in the lithium deposition area and use a punching machine to punch it out. disc (i.e. S = 0.1256cm2), The disc (test sample) is placed flat in an aluminum crucible (bottom inner diameter is 4mm) to keep the disc in full contact with the bottom of the crucible, and the lid is closed. The mass of the test sample is weighed and recorded on a balance, 2.11mg (m), and then the aluminum crucible is placed on a differential scanning calorimeter (DSC) for testing. The test parameters are: test temperature is 35-200℃, temperature rise rate is 5℃ / min, carrier gas atmosphere is 99.99% helium, and carrier gas flow rate is 60ml / min. Figure 1 By integrating the characteristic peak area of ​​lithium precipitation in the DSC curve at 180°C, the melting enthalpy ΔH1 per unit mass of the test sample is obtained to be 0.0603 g / J. By the formula: The amount of lithium deposited on the anode surface Δm is calculated to be 2.32ug / cm 2 The amount of lithium deposition accounts for 0.0138wt%.

[0038] Example 2

[0039] The lithium-ion battery was charged to 100% SOC at 0℃2.5C, and then discharged to 0% SOC at 1C, cycled for 10 weeks, and finally discharged to 0% SOC at 1C, moved into a glove box for disassembly, and the anode electrode piece with lithium deposition was taken out. The anode electrode piece was immersed in a pure DMC solution for 0.5h, and then allowed to stand at room temperature and vacuum for 0.5h to remove residual electrolyte and DMC. During the above process, the anode electrode piece could not contact air and water. The anode electrode piece was then moved into a glove box for sample preparation. In the glove box, the anode electrode piece in the lithium deposition area was selected and punched out using a punching machine. disc (i.e. S = 0.1256cm2), The disc (test sample) is placed flat in an aluminum crucible (bottom inner diameter is 4mm) to keep the disc in full contact with the bottom of the crucible, and the lid is closed. The mass of the test sample is weighed and recorded on a balance, 2.08mg (m), and then the aluminum crucible is placed on a differential scanning calorimeter (DSC) for testing. The test parameters are: test temperature is 35-200℃, temperature rise rate is 5℃ / min, carrier gas atmosphere is 99.99% helium, and carrier gas flow rate is 60ml / min. By integrating the characteristic peak area of ​​lithium precipitation of the DSC curve in the range of 180℃, the melting enthalpy ΔH1 per unit mass of the test sample is obtained to be 0.0455g / J, and the formula is: The amount of lithium deposited on the anode surface Δm is calculated to be 1.72ug / cm 2 The amount of lithium deposition accounts for 0.0104wt%.

[0040] Example 3

[0041] The lithium-ion battery was charged to 100% SOC at 0℃1.5C, then discharged to 0% SOC at 1C, cycled for 10 weeks, and finally discharged to 0% SOC at 1C, moved into a glove box for disassembly, and the anode electrode piece with lithium deposition was taken out. The anode electrode piece was immersed in a pure DMC solution for 0.5h, and then allowed to stand at room temperature and vacuum for 0.5h to remove residual electrolyte and DMC. During the above process, the anode electrode piece could not contact air and water. The anode electrode piece was then moved into a glove box for sample preparation. In the glove box, the anode electrode piece in the lithium deposition area was selected and punched out using a punching machine. disc (i.e. S = 0.1256cm2), The disc (test sample) is placed flat in an aluminum crucible (bottom inner diameter is 4mm) to keep the disc in full contact with the bottom of the crucible, and the lid is closed. The mass of the test sample is weighed and recorded on a balance, 2.05mg (m), and then the aluminum crucible is placed on a differential scanning calorimeter (DSC) for testing. The test parameters are: test temperature is 35-200℃, temperature rise rate is 5℃ / min, carrier gas atmosphere is 99.99% helium, and carrier gas flow rate is 60ml / min. By integrating the characteristic peak area of ​​lithium precipitation of the DSC curve in the range of 180℃, the melting enthalpy ΔH1 per unit mass of the test sample is obtained to be 0.0308g / J, and the formula is: The amount of lithium deposited on the anode surface Δm is calculated to be 1.15ug / cm 2 The amount of lithium deposition accounts for 0.0070wt%.

[0042] Example 4

[0043] The lithium-ion battery was charged to 100% SOC at 0℃1.2C, then discharged to 0% SOC at 1C, cycled for 10 weeks, and finally discharged to 0% SOC at 1C, moved into a glove box for disassembly, and the anode electrode piece with lithium deposition was taken out. The anode electrode piece was immersed in a pure DMC solution for 0.5h, and then allowed to stand at room temperature and vacuum for 0.5h to remove residual electrolyte and DMC. During the above process, the anode electrode piece could not contact air and water. The anode electrode piece was then moved into a glove box for sample preparation. In the glove box, the anode electrode piece in the lithium deposition area was selected and punched out using a punching machine. disc (i.e. S = 0.1256cm2), The disc (test sample) is placed flat in an aluminum crucible (bottom inner diameter is 4mm) to keep the disc in full contact with the bottom of the crucible, and the lid is closed. The mass of the test sample is weighed and recorded on a balance, 2.17mg (m), and then the aluminum crucible is placed on a differential scanning calorimeter (DSC) for testing. The test parameters are: test temperature is 35-200℃, temperature rise rate is 5℃ / min, carrier gas atmosphere is 99.99% helium, and carrier gas flow rate is 60ml / min. By integrating the characteristic peak area of ​​lithium precipitation of the DSC curve in the range of 180℃, the melting enthalpy ΔH1 per unit mass of the test sample is obtained to be 0.0140g / J, and the formula is: The amount of lithium deposited on the anode surface Δm is calculated to be 0.55ug / cm 2 The amount of lithium deposition accounts for 0.0032wt%.

[0044] Verification process of Example 4 (lower limit): In an inert atmosphere glove box, 0 mg, 0.02 mg, 0.05 mg, 0.1 mg, and 0.2 mg of pure metallic lithium powder were mixed with 100 mg of graphite and placed in a crucible. The crucible was sealed and tested, and the corresponding ΔS was 0 J / g, 0.0981 J / g, 0.1724 J / g, 0.4203 J / g, and 0.9401 J / g, respectively. The linear fitting curve of the theoretical lithium precipitation amount and the measured lithium precipitation amount was obtained (see Figure 4 );

[0045] Example 5

[0046] The lithium-ion battery was charged to 100% SOC at 0℃5C, then discharged to 0% SOC at 1C, cycled for 30 weeks, and finally discharged to 0% SOC at 1C, moved into a glove box for disassembly, and the anode electrode piece with lithium deposition was taken out. The anode electrode piece was immersed in a pure DMC solution for 0.5h, and then allowed to stand at room temperature and vacuum for 0.5h to remove residual electrolyte and DMC. During the above process, the anode electrode piece could not contact air and water. The anode electrode piece was then moved into a glove box for sample preparation. In the glove box, the anode electrode piece in the lithium deposition area was selected and punched out using a punching machine. disc (i.e. S = 0.1256cm2), The disc (test sample) is placed flat in an aluminum crucible (bottom inner diameter is 4mm) to keep the disc in full contact with the bottom of the crucible, and the lid is closed. The mass of the test sample is weighed and recorded on a balance, 2.46mg (m), and then the aluminum crucible is placed on a differential scanning calorimeter (DSC) for testing. The test parameters are: test temperature is 35-200℃, temperature rise rate is 5℃ / min, carrier gas atmosphere is 99.99% helium, and carrier gas flow rate is 60ml / min. By integrating the characteristic peak area of ​​lithium precipitation of the DSC curve in the range of 180℃, the melting enthalpy ΔH1 per unit mass of the test sample is obtained to be 106.1255g / J, and the formula is: The amount of lithium deposited on the anode surface Δm is calculated to be 4751.45 g / cm 2 The lithium deposition amount accounts for 24.3wt%.

[0047] Verification process of Example 5 (upper limit): In an inert atmosphere glove box, 0 mg, 0.37 mg, 0.44 mg, 0.55 mg, and 0.72 mg of pure metallic lithium powder were mixed with 2 mg of graphite and placed in a crucible. The crucible was sealed and tested, and the corresponding ΔS was 0 J / g, 62.0523 J / g, 79.2925 J / g, 84.8427 J / g, and 112.3242 J / g, respectively. The linear fitting curve of the theoretical lithium precipitation amount and the measured lithium precipitation amount was obtained (see Figure 5 );

[0048] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for quantitatively detecting the amount of lithium deposition in a lithium ion battery, characterized in that: The quantitative detection method comprises the following steps: S100: Cycle the lithium-ion battery to be tested to a preset SOC, and disassemble it to obtain an anode electrode sheet; S200: removing residual electrolyte from the anode electrode piece in step S100 to obtain an electrode piece to be tested; S300: cutting the electrode to be tested in step S200 to obtain a test sample, and obtaining the quality of the test sample; S400: The test sample in step S300 is measured by a differential scanning calorimeter to obtain a DSC curve, and the melting enthalpy per unit mass of the test sample is obtained by integrating the characteristic peaks of the DSC curve in the range of 175 to 185° C.; S500: Calculate the lithium deposition amount of the lithium-ion battery according to the melting enthalpy per unit mass of the test sample.

2. The quantitative detection method according to claim 1, characterized in that: In step S100, cycling the lithium-ion battery to be tested to a preset SOC includes: The lithium-ion battery to be tested is charged to 100% SOC at 1-5C at 0-5°C, then discharged to 0% SOC at 1-1.5C, cycled for 5-50 cycles, and finally discharged to 0% SOC at 1-1.5C.

3. The quantitative detection method according to claim 2, characterized in that: In step S100, cycling the lithium-ion battery to be tested to a preset SOC includes: The lithium-ion battery to be tested is charged to 100% SOC at 0°C 1-5C, then discharged to 0% SOC at 1C, cycled for 10-30 cycles, and finally discharged to 0% SOC at 1C.

4. The quantitative detection method according to claim 1, characterized in that: In step S200, removing residual electrolyte from the anode electrode in step S100 includes: At an ambient temperature of 18 to 35° C., the anode electrode sheet is immersed in an organic solvent for 0.5 to 1 hour, and then placed in a vacuum environment and allowed to stand for 0.5 to 1 hour.

5. The quantitative detection method according to claim 1, characterized in that: In step S300, cutting the electrode to be tested to obtain a test sample comprises: The electrode piece to be tested is cut according to the size of the test crucible so that the cut test piece is in full contact with the bottom of the crucible and sealed to obtain a sample crucible.

6. The quantitative detection method according to claim 1, characterized in that: In step S400, the parameters of the differential scanning calorimeter during the measurement process include: Test temperature: 35~200℃; Temperature rise rate: 5~15℃ / min; Carrier gas atmosphere: inert atmosphere; Carrier gas flow rate: 20~120ml / min.

7. The quantitative detection method according to claim 6, characterized in that: The parameters of the differential scanning calorimeter during the measurement process include: Test temperature: 35~200℃; Temperature rise rate: 5℃ / min; Carrier gas atmosphere: 99.99% helium; Carrier gas flow rate: 60ml / min.

8. The quantitative detection method according to claim 1, characterized in that: The mass of the sample to be tested is recorded as m (mg), the melting enthalpy per unit mass of the sample to be tested is recorded as ΔH1 (J / g), the theoretical melting enthalpy of lithium is recorded as ΔH0 (J / g), and the area of ​​the sample to be tested is recorded as S (cm 2 ), the amount of lithium precipitated from the lithium ion battery is recorded as Δm (ug / cm 2 ), Δm is calculated by formula I; Among them, δ is the correction factor of 0.8 and ΔH0 is 350 J / g.

9. The quantitative detection method according to claim 1, characterized in that: The detection range of the lithium ion battery lithium deposition amount is: Based on the total mass of the active material layer in the sample to be tested, the mass percentage of lithium deposition is 0.003-30wt%.

10. The quantitative detection method according to claim 1, characterized in that: In step S400, When the number of the test sample is 1, the melting enthalpy per unit mass of the test sample is obtained by integrating the characteristic peaks existing in the range of 175 to 185° C. obtained by measuring the test sample by a differential scanning calorimeter on the DSC curve; When the number of the test samples is greater than or equal to 2, the melting enthalpy per unit mass of the test samples is obtained by measuring each of the test samples by differential scanning calorimetry to obtain multiple DSC curves, integrating the characteristic peaks of each DSC curve in the range of 175 to 185°C in turn, and then adding the integrated areas.

Citation Information

Cited By

  • Method for detecting lithium precipitation amount of lithium ion battery

    CN121324945A

  • Dendritic crystal in-situ quantitative detection system and detection method based on battery internal distributed micro-area capacitance detection

    CN121324997A